Balancing co-benefits and trade-offs between climate change mitigation and adaptation innovations under mixed crop-livestock systems in semi-arid Zimbabwe - Sabine Homann-Kee Tui; Roberto O. Valdivia; Katrien Descheemaeker; Gevious Sisito; Elisha N. Moyo; Farai Mapanda (CABI Agriculture and Bioscience)
Abstract Achieving Zimbabwe’s national and international commitments to food systems transformation and climate resilience building is of high priority. Integrated simulation-based research approaches developed under the Agricultural Model Intercomparison and Improvement Project (AgMIP) are important sources of evidence to guide policy decisions towards sustainable intensification. Through the identification of economically viable, socially inclusive and environmentally sustainable development pathways, the analysis in this study evaluates co-benefits and trade-offs between climate change adaptation and mitigation interventions for vulnerable smallholder crop-livestock holdings in the semi-arid regions of Zimbabwe. We explore how climate effects disrupt the livelihoods and food security for diverse farm types, the extremely vulnerable and those better resource endowed but facing high risks. In an iterative process with experts and stakeholders, we co-developed context specific development pathways. They include market-oriented adaptation and mitigation interventions and social protection mechanisms that would support the transition towards more sustainable intensified, diversified and better integrated crop-livestock systems. We assess the trade-offs associated with adoption of climate-smart interventions aimed at improving incomes and food security but that may have consequences on GHG emissions for the different pathways and farm types. The approach and results inform the discussion on drivers that can bring about sustainable intensification, and the extent to which socio-economic benefits could enhance the uptake of emission reducing technologies thereof. Through this strategy we evaluate interventions that can result in win–win outcomes, that is, adaptation-mitigation co-benefits, and what this would imply for policies that aim at transforming agri-food systems.